Pengembangan Media Pembelajaran Big Snake And Ladder Game Berbasis Budaya Palembang pada Materi Bilangan Bulat untuk Siswa Kelas VII SMP - Roshalita, Nabila; Yuliani, Refi Elfira; Rizta, Amrina (Universitas Muhammadiyah Palembang, 2025)
Mathematics is one of the of the most important subjects in elementary through high school education. Learning media is one of the as a tool in activities in the teaching and learning process. This research aims to see the process and produce learning media big snake and ladder game based on Palembang culture.Palembang integer material for VII grade junior high school students that are valid and practical. This type of research is Development research ADDIE model (Analysis, Design,Development, Implementation, Evaluation). The subjects used were students of Class VII.7 at SMP Negeri 26 Palembang with a total of 26 students. Data collection techniques using Using walk-through and questionnaire sheets. Validation stage on Development of big snake and ladder game learning media on integers. Integers for VII grade junior high school students through 2 stages of validation. The research Developed is declared good quality with the following results: 1) Validity test with an average score of 83.76% with the criteria “very valid”; 2) Practicality test with an average teacher response score of 83.33% and an average student response score of (small group) 92% with the criteria “very practical” as well as the average rating of the students’ response in the large group test (field test). Large group test (field test) 85.81% with “very practical” criteria.